OPERATION OPTIMIZATION ASSISTANCE SYSTEM AND OPERATION OPTIMIZATION ASSISTANCE METHOD - NOGUCHI, Junji; KAKUTANI, Yuji; FUJISHIRO, Takahiro; YAMASAKI, Masami (2016)
Provided is an operation optimization assistance system having a machine, a production/operation management device for managing production/operation of the machine, a production/operation planning device for planning the production/operation of the machine, and a maintenance management device for managing a running state and a running risk of the machine, wherein the maintenance management device detects a failure presage of the machine, and the production/operation management device uses a production/operation plan managed by the production/operation planning device and the running risk managed by the maintenance management device to create a countermeasure against the failure presage detected by the maintenance management device. L'invention concerne un système d'assistance à l'optimisation d'opération ayant une machine, un dispositif de gestion de production/opération destiné à gérer la production/l'opération de la machine, un dispositif de planification de production/opération destiné à planifier la production/l'opération de la machine et un dispositif de gestion de maintenance destiné à gérer un état de fonctionnement et un risque de fonctionnement de la machine, le dispositif de gestion de maintenance détectant un présage de dysfonctionnement de la machine et le dispositif de gestion de production/opération utilisant un plan de production/opération géré par le dispositif de planification de production/opération et le risque de fonctionnement géré par le dispositif de gestion de maintenance pour créer une contre-mesure contre le présage de dysfonctionnement détecté par le dispositif de gestion de maintenance. 機械と、前記機械の生産・運行を管理する生産・運行管理装置と、前記機械の生産・運行を計画する生産・運行計画装置と、前記機械の稼動状態や稼動リスクを管理する保守管理装置と、を有する運行最適化支援システムは、前記保守管理装置が、前記機械の故障予兆を検知し、前記生産・運行管理装置が、前記生産・運行計画装置の管理する生産・運行計画、及び、前記保守管理装置の管理する稼動リスクを用いて、前記保守管理装置により検知された故障予兆に対する対策案を作成する。